Development of a conceptual model of the notion of "Chemical Technology Equipment - Shaposhnyk, A. M.; Lazarieva, T. A. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the development of conceptual thinking of future specialists in the chemical industry. Conceptual thinking can be considered as the content or a way of thinking. The paper identifies three types of conceptual skills, namely semantic, categorical and conceptual, whose formation and development create the conditions for modern professional training of future specialists in the chemical industry. The article also theoretically substantiates and presents a conceptual model of the notion of "Chemical Technology Equipment". Control questions may be applied to determine a number of characteristics of the equipment. The authors theoretically substantiated a number of the characteristics of the functions of the equipment to carry out mechanical and hydro-mechanical, thermal and refrigeration processes, as well as chemical mass transfer processes. The paper suggests a set of characteristics of the structure of the equipment, namely a number of characteristics of the concepts of "traffic source", "power supply device", "gear", "actuator", "working body", "management tool", " regulation tool", "protection tool", "alarm tool", "operation safety device". The development of a number of characteristics of the mechanisms and principles of operation of the equipment was justified. The article defines characteristics, criteria and parameters of the equipment, namely geometric, physical and mechanical, technological, reliability and durability, power, operational, economic, standardization and unification, transportability and storage, environmental, safety, aesthetic and ergonomic, which are taken into account while selecting chemical technology equipment.